DIAGNOSA GEJALA PENYAKIT DIARE PADA ANAK BALITA MENGGUNAKAN SISTEM PAKAR - Asnawati, Asnawati; EiCheng, EiCheng; Rosdiana, Rosdiana (Jurnal Media Infotama, 2012)
Diagnosing against viruses and bacteria in infants should be done as quickly and accurately as possible , because viruses and bacteria in infants can quickly spread and attack the nearest whole person . In this case the role of a highly reliable expert to mendiagonosa and determine the type of virus and bacteria , and provide examples of how the response to get the best solution . In general , expert systems are seeking to adopt a system of human knowledge into a computer that is designed to model the ability to solve problems like an expert . With this expert system , ordinary people can solve the problem or just looking for a real quality information that can only be obtained with the help of experts in the field . Expert system application program to detect diarrheal disease in young children by the method of this rule -based approaches , is used to provide alternative information to patients to detect diarrheal disease in infants . Program expert system to detect diarrheal disease in young children by the method of rule -based approaches were created using Visual Basic software can be used as a diarrheal disease detection and information used in health centers gods fence.